2002
DOI: 10.1046/j.1360-0443.2002.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy of prescription and over‐the‐counter nicotine replacement therapy

Abstract: Smoking cessation rates achieved with nicotine gum and patch under OTC conditions were as good as those under real-world prescribing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 31 publications
3
90
0
Order By: Relevance
“…The drug is underused to an extent similar to that seen with oral nicotine replacement. 31 More frequent contacts during the first few weeks of treatment may improve treatment adherence and increase the chance that patients benefit from the medication.…”
Section: Discussionmentioning
confidence: 99%
“…The drug is underused to an extent similar to that seen with oral nicotine replacement. 31 More frequent contacts during the first few weeks of treatment may improve treatment adherence and increase the chance that patients benefit from the medication.…”
Section: Discussionmentioning
confidence: 99%
“…The switch to OTC status for these products increased the use of NRT in the U.S. by 152% (2), and this increased use has been maintained for several years (3). Several randomized placebo-controlled trials showed the efficacy of the nicotine patch under simulated OTC conditions with minimal behavioral support and product instruction (4)(5)(6), reducing concerns that OTC NRT would not be as effective as prescription NRT (7,8). Better access to NRT was also expected to improve rates of smoking cessation in the U.S. (9).…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to smoking cessation treatment under these circumstances can be challenging. Within the general population, those who do adhere to recommended treatment usually achieve better cessation outcomes ( Lam, Abdullah, Chan, & Hedley, 2005 ;Shiffman et al, 2002 ). To date , there are no controlled trials among homeless persons of interventions to improve adherence to self-administered medications, such as nicotine replacement therapy (NRT) .…”
Section: Introductionmentioning
confidence: 99%